The Application of Biocatalysis in the Preparation and Resolution of Morita‐Baylis‐Hillman Adducts and Their Derivatives. (6th December 2021) - Juma, Wanyama Peter; Nyoni, Dubekile; Brady, Dean; Bode, Moira L.
Abstract: The Morita‐Baylis‐Hillman (MBH) reaction affords highly functionalised allylic alcohols containing a new stereogenic centre. These MBH adducts are very versatile and have been transformed into a large range of products, some of which have medicinal potential. Several examples of asymmetric syntheses of MBH adducts have been reported, although a generally applicable method remains to be developed. Biocatalytic approaches for the synthesis and enzymatic kinetic resolution of MBH adducts have been reported, and are discussed in detail in this review. Enzymes able to catalyse the asymmetric MBH reaction have been identified, but selectivity and efficiency have generally been low. Lipases, esterases and nitrile‐converting enzymes have all been successfully applied in the resolution of MBH adducts, with excellent selectivity being realised in most cases. Abstract : The Morita‐Baylis‐Hillman reaction is an important carbon‐carbon bond forming reaction in organic synthesis. A new stereogenic centre is created in this reaction and much effort has been invested over the years into finding methods for the preparation of enantiomerically pure or enantiomerically enriched Morita‐Baylis‐Hillman products. In this review, the contribution of biocatalysis towards achieving this goal is discussed.